Twenty Years’ Development of Teacher Identity Research: A Bibliometric Analysis - Zhang, Yunyun; Wang, Ping (Frontiers in Psychology, 2022)
This paper aims to demonstrate a detailed knowledge map of the teacher identity research via a 20-year data set from the Web of Science database. A bibliometric analysis was employed for analyzing articles published between 2001 and 2021 to show the status of teacher identity research during the past 20 years, research topics on teacher identity, and future research directions. Using the keyword “teacher identity” and filtering data by selecting articles and early access in teaching and education, 848 papers were retrieved. Through production, content, and citation analysis with the help of the bibliometric tool, this paper found that teacher identity remained a popular research theme in the academic field during the past twenty years, and its booming production involved many authors, institutions, and sources, and countries. Furthermore, teachers’ “beliefs,” “emotions,” “professional development,” and “context” impacting the construction and reconstruction of teacher identity were popular topics in teacher identity research, and fundamental issues, including “identity,” “teacher identity,” “professional identity,” “development,” “teacher development,” “beliefs,” and “intersectionality” of teacher identity keep good topics in future research.